Opportunities to learn and barriers to change: crack cocaine use in the Downtown Eastside of Vancouver - Moffat Barbara; Johnson Joy L; Boyd Susan (BMC, 2008)
Abstract In 2004, a team comprised of researchers and service providers launched the Safer Crack Use, Outreach, Research and Education (SCORE) project in the Downtown Eastside of Vancouver, British Columbia, Canada. The project was aimed at developing a better understanding of the harms associated with crack cocaine smoking and determining the feasibility of introducing specific harm reduction strategies. Specifically, in partnership with the community, we constructed and distributed kits that contained harm reduction materials. We were particularly interested in understanding what people thought of these kits and how the kits contents were used. To obtain this information, we conducted 27 interviews with women and men who used crack cocaine and received safer crack kits. Four broad themes were generated from the data: 1) the context of crack use practices; 2) learning/transmission of harm reducon education; 3) changing practice; 4) barriers to change. This project suggests that harm reduction education is most successful when it is informed by current practices with crack use. In addition it is most effectively delivered through informal interactions with people who use crack and includes repeated demonstrations of harm reduction equipment by peers and outreach workers. This paper also suggests that barriers to harm reduction are systemic: lack of safe housing and private space shape crack use practices.